(untitled) (Proceedings of International Educators Conference, 2023)
In this article, the diagnosis of allergic rhinitis in children with bronchial asthma comorbidity, using a specially developed questionnaire, based on allergy anamnesis was considered. A retrospective study was conducted included 82 patients aged 2-13 years. From the medical history and outpatient map studied demographic characteristics: age, gender, place of residence, clinical characteristics: duration of disease, severity of AR and course of AR according to the classification of ARIA, 2018 ( Allergic Rhinitis and Impaction Asthma), concomitant allergic diseases the severity of bronchial asthma was determined according to the classification of GINA, 2016.